Density Functional Investigation of the Inclusion of Gold Clusters on a CH3S Self-Assembled Lattice on Au(111). (17th October 2016) - Allen, Darnel J.; Archibald, Wayne E.; Harper, John A.; Saputo, John C.; Torres, Daniel
Abstract : We employ first-principles density functional theoretical calculations to address the inclusion of gold (Au) clusters in a well-packed CH3 S self-assembled lattice. We compute CH3 S adsorption energies to quantify the energetic stability of the self-assembly and gold adsorption and dissolution energies to characterize the structural stability of a series of Au clusters adsorbed at the SAM-Au interface. Our results indicate that the inclusion of Au clusters with less than four Au atoms in the SAM-Au interface enhances the binding of CH3 S species. In contrast, larger Au clusters destabilize the self-assembly. We attribute this effect to the low-coordinated gold atoms in the cluster. For small clusters, these low-coordinated sites have significantly different electronic properties compared to larger islands, which makes the binding with the self-assembly energetically more favorable. Our results further indicate that Au clusters in the SAM-Au interface are thermodynamically unstable and they will tend to dissolve, producing Au adatoms incorporated in the self-assembly in the form of CH3 S-Au-SCH3 species. This is due to the strong S-Au bond which stabilizes single Au adatoms in the self-assembly. Our results provide solid insight into the impact of adatom islands at the CH3 S-Au interface.